Hemiparetic multiple sclerosis. Issue 8 (August 1990) - Cowan, J; Ormerod, I E; Rudge, P
Abstract : Eight patients are described who presented with hemiparesis which involved the face in seven. Six of the eight subsequently developed clinically definite multiple sclerosis and in the remaining two patients multiple sclerosis was the likely diagnosis. Magnetic resonance imaging gave useful information about the site of the lesions responsible for the presenting syndrome and provided additional information in support of a diagnosis of multiple sclerosis.